(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In India banking industry has elaborated various financial rearrangement that would create a shift from all the traditional banking approaches to digitalized banking services to gratify the customers requirements. Mobile banking in India is increasing rapidly because customers finds it more easy and comfortable way for doing banking transactions. Thus digitalized banking services has taken a step further in its digital platform through applications to access account information and other services provided by the banks. This type of digitalized banking services will diminish branch level transaction and in due course of time it will make ease for customer service pressure, thus declines the operating cost for banks. In this I study about customer’s satisfaction and perception towards mobile banking. The operational strike on black money known as demonetization which made a dramatic change in the functioning as well as products and services of banks. With this respect my study shows the relevance of customer perception towards mobile banking.